thùy linh

bài 4 phân tích đa thức thành nhân tử

d, \(x^2\left(y-z\right)+y^2\left(z-x\right)+z^2\left(x-y\right)\)

e,\(x^2-15x+36\)

f,\(x^{12}-3x^6y^6+2y^{12}\)

g,\(x^8-64x^2\)

h,\(\left(x^2-8\right)^2-784\)

Nguyễn Lê Phước Thịnh
22 tháng 11 lúc 13:06
e: =x^2-12x-3x+36=(x-3)(x-12)f: \(=x^{12}-x^6y^6-2x^6y^6+2y^{12}\)\(=x^6\left(x^6-y^6\right)-2y^6\left(x^6-y^6\right)\)\(=\left(x^6-2y^6\right)\left(x-y\right)\left(x+y\right)\left(x^2-xy+y^2\right)\left(x^2+xy+y^2\right)\)g: \(=x^2\left(x^6-64\right)\)\(=x^2\left(x-2\right)\left(x+2\right)\left(x^2+2x+4\right)\left(x^2-2x+4\right)\)
Đọc tiếp
Bình luận (0)
Vũ Thị Minh Ánh
22 tháng 11 lúc 13:52
a) \(x^2\left(y-z\right)+y^2\left(z-x\right)+z^2\left(x-y\right)\)\(=x^2y-x^2z+y^2z-y^2x+z^2\left(x-y\right)\)\(=\left(x^2y-y^2x\right)-\left(x^2z-y^2z\right)+z^2\left(x-y\right)\)\(=xy\left(x-y\right)-z\left(x-y\right)\left(x+y\right)+z^2\left(x-y\right)\)\(=\left(x-y\right)\left(xy-xz-yz+z^2\right)\)\(=\left(x-y\right)\left[x\left(y-z\right)-z\left(y-z\right)\right]\)\(=\left(x-y\right)\left(y-z\right)\left(x-z\right)\)h) \(\left(x^2-8\right)^2-784=\left(x^2-8\right)^2-28^2\)\(=\left(x^2-8-28\...
Đọc tiếp
Bình luận (1)

Các câu hỏi tương tự
Ut02_huong
Xem chi tiết
Hoàng Ngọc Tuyết Nhung
Xem chi tiết
Phương Trần Lê
Xem chi tiết
Username2805
Xem chi tiết
bạch thục quyên
Xem chi tiết
Ut02_huong
Xem chi tiết
Huỳnh Kim Bích Ngọc
Xem chi tiết
Hoàng Ngọc Tuyết Nhung
Xem chi tiết
Aeris
Xem chi tiết
Thuỳ
Xem chi tiết

Khoá học trên OLM (olm.vn)


Khoá học trên OLM (olm.vn)